Classical Ehlers‐Danlos syndrome with a propensity to arterial events: A new report on a French family with a COL1A1 p.(Arg312Cys) variant. Issue 2 (1st October 2019) - Adham, Salma; Dupuis‐Girod, Sophie; Charpentier, Etienne; Mazzella, Jean‐Michaël; Jeunemaitre, Xavier; Legrand, Anne
Abstract: Ehlers‐Danlos syndromes (EDS) are a clinically and genetically heterogeneous group of connective tissue disorders. Overlapping features including arterial aneurysms/dissections in both classical and vascular EDS are a major challenge in the clinical diagnosis of these subtypes. The COL1A1 p.(Arg312Cys) variant leads to a phenotype of classical EDS with a propensity to arterial complications. Our report describes a two‐generation family with one individual presenting with a dissection of the right external iliac artery. The primary suspicion of vascular EDS with the unsatisfactory identification of a COL3A1 benign variant was secondarily readjusted with the identification of COL1A1 p.(Arg312Cys) variant. This raises the question of the association of COL1A1 p.(Arg312Cys) with arterial complications and the need for a gene panel including not only the usual genes tested in search of classical or vascular EDS but also COL1A1 . Abstract : Evocative arterial history along with overlapping classical and vascular EDS phenotype should lead to perform a new gene panel including COL5A1, COL5A2, COL3A1 and COL1A1.